Disclosure and social isomorphism in companies listed in corporate sustainability index - Mapurunga, Patrícia Vasconcelos Rocha; Correia-Lima, Bruno Chaves; Holanda, Allan Pinheiro (Revista de Administração da UFSM, 2015)
The objective of the research is to examine the existence of social disclosure practices in companies that compose the ISE under the approach of isomorphism, in other words, we compared the disclosure or not a particular social practice by major companies comprising the ISE are also disclosed by other companies. Adopted the metric proposed by Vieira (2006) to measure social disclosure, the metric is composed of 16 disclosure items relating to social information to be disclosed in the Annual Reports of the companies. The group of "major companies" was composed by the Bank Brazil SA (1st Place) and Banco Bradesco SA (2nd Place). The sample was composed of 37 public companies listed on the ISE in version 2010/2011. The results provide subsidies to non-rejection of the hypothesis that the larger companies will be followed by other companies as the disclosure of social information.